Cultural Contents of The Bright an English Textbook For Junior High School - Ni Made Meyra Reditya Devi; Dewa Putu Ramendra; I Nyoman Pasek Hadi Saputra (Universitas Pendidikan Ganesha, 2023)
Textbooks often need to portray the target culture accurately. This study aims to discover the cultural categories and how they are represented in the cultural dimensions in the “Bright an English” textbook for grade VII of junior high school. This research uses a qualitative content analysis approach. The data were collected through document analysis and analyzed using and recording data, systematic coding, category creation, and interpretation. This study resulted in two main findings. First, cultural categories were found in full in the textbooks but in unbalanced proportions. This shows the dominance of local culture and the lack of representation of international culture. Second, the representation of cultural categories in the cultural dimension also varies. Representations in the textbooks appear through textual data (words, sentences, dialogues, readings) and image data. Five cultural dimensions (products, practices, perspectives, communities, and individuals) are fully represented in the target culture and international culture through textual data. Meanwhile, in the textual data, the local culture does not show the dimension of perspective. Representation in the form of image data is fully present in the local culture. In the image data, the target culture does not show the dimensions of perspective and community, and the international culture does not show the dimensions of practice and perspective. In conclusion, there are potential imbalances in the representation of global culture that can be addressed to increase the cultural diversity presented to students.